2015
DOI: 10.1016/j.bjane.2013.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between fast and slow induction of propofol given by target-controlled infusion: expected propofol concentration at the effect site. Randomized controlled trial

Abstract: Background and objective: Studies have shown that the rate of propofol infusion may influence the predicted propofol concentration at the effect site (Es). The aim of this study was to evaluate the Es predicted by the Marsh pharmacokinetic model (ke0 0.26 min −1 ) in loss of consciousness during fast or slow induction. Method: The study included 28 patients randomly divided into two equal groups. In slow induction group (S), target-controlled infusion (TCI) of propofol with plasma, Marsh pharmacokinetic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
1
3
0
1
Order By: Relevance
“…They found that, with fast k e0 s of 0.45 min À1 with the Schnider model and 1.21 min À1 with the Marsh model, Ce CALC values after a rapid infusion were greater than those observed after a slow infusion, whereas the opposite was seen with the slower k e0 of 0.26 min À1 using the original Marsh model. Similar results were obtained in another study with the Marsh model and a k e0 of 0.26 min À1 [19] and a marked difference in predicted effect site concentrations at loss of consciousness was seen with the Marsh model and k e0 s of 0.26 min À1 or 1.2 min À1 [20]. The results of our simulations of the two infusion rates used (Table 4) replicate the results with the model/k e0 combinations studied in the original study of Sepulveda.…”
Section: Discussionsupporting
confidence: 89%
“…They found that, with fast k e0 s of 0.45 min À1 with the Schnider model and 1.21 min À1 with the Marsh model, Ce CALC values after a rapid infusion were greater than those observed after a slow infusion, whereas the opposite was seen with the slower k e0 of 0.26 min À1 using the original Marsh model. Similar results were obtained in another study with the Marsh model and a k e0 of 0.26 min À1 [19] and a marked difference in predicted effect site concentrations at loss of consciousness was seen with the Marsh model and k e0 s of 0.26 min À1 or 1.2 min À1 [20]. The results of our simulations of the two infusion rates used (Table 4) replicate the results with the model/k e0 combinations studied in the original study of Sepulveda.…”
Section: Discussionsupporting
confidence: 89%
“…Target controlled infusion systems, usually make use of syringe pumps with maximum infusion rates between 10 and 160 mg/kg/h. 60 In our simulations, we considered 85 mg/kg/h as the upper bound on the infusion rate, which is converted to u max =200 mg/min (= 3.3 mg/sec), considering a heavy patient weighted 140 kg. It should be noted, however, that the actual infusion rates computed by the controllers are much lower than this bound, which agrees with other observations reported in the literature.…”
Section: Constrained Mpc Problemmentioning
confidence: 99%
“…Because of the negligible volume of the effect-site abstract compartment, the constants k 1e and k e0 are equal [9,14]. The PK parameters depend on the patient's characteristics only such as age, gender, height, and weight [9,10,14,15].…”
Section: The Patient Modelmentioning
confidence: 99%
“…9 and considering the adjustment mechanism from Eq. 6, the variation of the controller's parameters k p and k i is [15]: where p = d∕dt.…”
Section: Mrac-pi and Mrac-pi λ Controllers Designmentioning
confidence: 99%